Evidence for direct cognitive control of fixation durations during reading. (February 2015) - Rayner, Keith; Reingold, Eyal M
Highlights: Discusses the direct control of eye fixations in reading. Reviews evidence showing that fixation durations are controlled on a moment-to-moment basis. Provides evidence in favor of direct control during reading. Abstract : The control of eye movements during reading is discussed with emphasis on the direct cognitive-control hypothesis. According to this hypothesis, the durations of eye fixations are controlled on a moment-to-moment basis by cognitive processes associated with processing the lexical and linguistic properties of the fixated word. When the critical role of parafoveal lexical processing is taken into account, the tight timing constraints imposed by neural delays are not inconsistent with the direct cognitive control hypothesis. Several convergent lines of research using distributional analysis techniques and gaze-contingent display change paradigms are reviewed which provide strong support for the validity of the hypothesis. It is concluded that eye movements and gaze contingent display paradigms offer cognitive neuroscience promising avenues for understanding not only reading but on-line processing activities in a number of different tasks.